“Suddenly, it was a real thing”: The Feminist Fight for Equal Opportunities in the Canadian Broadcasting Corporation, 1971-1981 - Freeman, Barbara (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2019)
Following the recommendations of the Royal Commission on the Status of Women in 1970, feminist activists spent the next decade fighting for gender equity in federal workplaces, including the Canadian Broadcasting Corporation. They argued that equal opportunity in hiring and promotions would lead to more equitable and accurate representations of Canadian women on the air. After several encounters with these determined activists inside and outside of the Crown corporation, the CBC became an equal opportunity employer and adopted an affirmative action policy, while maintaining its own limited, corporate goals.